CONTRIBUTION OF THE ANDALUSIAN NAHWUU SCHOOL: ABU HAYAN'S TRENDS AND PERSPECTIVES IN THE DEVELOPMENT OF THE NAHWU - Budi, Rahmat Dinni Haerul; Pribadi, Mohammad (Al-Uslub: Journal of Arabic Linguistic and Literature, 2024)
Nahwuu science has experienced very rapid and significant progress in study and analysis. This is proven by the many schools of thought (schools) in the study of nahwuu science. During its early development, the science of nahwuu was dominated by two very popular schools of thought, namely the Bashroh School as the forerunner to the birth of the science of nahwuu, followed by the Kufah School. Subsequently, other madrasas emerged, such as the Baghdad School, the Andalusian School, and the Egyptian School. The method used is a qualitative method by carrying out categorization which is then interpreted descriptively-analytically. Anbu Hayan's criticism and lawsuit against nahwuu mostly touched on Imam Ibnu Malik's concept of Nahwuu.